Bonding performance of universal adhesives in different etching modes - Wagner, Anna; Wendler, Michael; Petschelt, Anselm; Belli, Renan; Lohbauer, Ulrich (Journal of Dentistry, 2014)
The aim of this study was to compare the microtensile bond strength (?TBS) and resin penetration into dentine of three universal adhesives (UAs) applied in two different etching modes (i.e. self-etch or etch-and-rinse). The effect of thermocycling on the ?TBS was also evaluated.The occlusal third of sound human molars was removed and the exposed surfaces were treated with three UAs (Futurabond Universal, Scotchbond Universal Adhesive and All-Bond Universal) in self-etch or etch-and-rinse mode. Two one-step self-etch adhesives (Futurabond DC and Futurabond M) were applied on additional teeth as reference. After composite build up, the specimens were stored for 24 h in distilled water at 37 °C or thermocycled for 5000 cycles. Composite/dentine beams were prepared (1 mm(2)) and ?TBS test was performed. Data was analyzed using three-way ANOVA and Tukey's test (?=0.05). One additional tooth was prepared for each group for evaluation of infiltration ability into dentine by dyeing the adhesives with a fluorochrome (Rhodamine B). After longitudinal sectioning, the generated interfaces were examined under confocal laser scanning microscopy.The addition of an etching step did not significantly affect the ?TBS of none of the UAs, when compared to their self-etch application mode. All pre-etched specimens showed considerably longer resin tags and thicker hybrid layers. Thermocycling had no significant effect on the ?TBS of the UAs.Application of an etching step prior to UAs improves their dentine penetration, but does not affect their bond strength to dentine after 24h or after thermocycling for 5000 cycles.Similar bond strength values were observed for the UAs regardless of application mode, which makes them reliable for working under different clinical conditions.
EVALuna2:24659

Detection of collagens by multispectral optoacoustic tomography as an imaging biomarker for Duchenne muscular dystrophy - Regensburger, Adrian; Fonteyne, Lina M.; Jüngert, Jörg; Wagner, Anna; Gerhalter, Teresa; Nagel, Armin Michael; Heiß, Rafael; Flenkenthaler, Florian; Qurashi, Matthias; Neurath, Markus; Klymiuk, Nikolai; Kemter, Elisabeth; et al. (Nature Medicine, 2019)
Biomarkers for monitoring of disease progression and response to therapy are lacking for muscle diseases such as Duchenne muscular dystrophy. Noninvasive in vivo molecular imaging with multispectral optoacoustic tomography (MSOT) uses pulsed laser light to induce acoustic pressure waves, enabling the visualization of endogenous chromophores. Here we describe an application of MSOT, in which illumination in the near- and extended near-infrared ranges from 680–1,100 nm enables the visualization and quantification of collagen content. We first demonstrated the feasibility of this approach to noninvasive quantification of tissue fibrosis in longitudinal studies in a large-animal Duchenne muscular dystrophy model in pigs, and then applied this approach to pediatric patients. MSOT-derived collagen content measurements in skeletal muscle were highly correlated to the functional status of the patients and provided additional information on molecular features as compared to magnetic resonance imaging. This study highlights the potential of MSOT imaging as a noninvasive, age-independent biomarker for the implementation and monitoring of newly developed therapies in muscular diseases.
CRIS-Team Scopus Importer:2019-12-17

Precision of handheld multispectral optoacoustic tomography for muscle imaging - Wagner, Anna; Danko, Vera; Federle, Anna; Klett, Daniel; Simon, David; Heiß, Rafael; Jüngert, Jörg M.; Uder, Michael; Schett, Georg; Neurath, Markus; Wölfle, Joachim; Waldner, Maximilian; et al. (Photoacoustics, 2021)
Photo-or optoacoustic imaging (OAI) allows quantitative imaging of target tissues. Using multi-wavelength illumination with subsequent ultrasound detection, it may visualize a variety of different chromophores at centimeter depth. Despite its non-invasive, label-free advantages, the precision of repeated measurements for clinical applications is still elusive. We present a multilayer analysis of n = 1920 imaging datasets obtained from a prospective clinical trial (NCT03979157) in n = 10 healthy adult volunteers. All datasets were analyzed for 13 single wavelengths (SWL) between 660 nm–1210 nm and five MSOT-parameters (deoxygenated/oxygenated/total hemoglobin, collagen and lipid) by a semi-automated batch mode software. Intraclass correlation coefficients (ICC) were good to excellent for intrarater (SWL: 0.82–0.92; MSOT-parameter: 0.72−0.92) and interrater reproducibility (SWL: 0.79−0.87; MSOT-parameter: 0.78−0.86), with the exception for MSOT-parameter lipid (interrater ICC: 0.56). Results were stable over time, but exercise-related effects as well as inter-and intramuscular variability were observed. The findings of this study provide a framework for further clinical OAI implementation.
CRIS-Team Scopus Importer:2020-12-25
Keywords: MSOT; Multispectral optoacoustic tomography; Muscle imaging; Optoacoustics; Photoacoustics

Self-adhesive resin cements: adhesive performance to indirect restorative ceramics - Zorzin, José Ignacio; Belli, Renan; Wagner, Anna; Petschelt, Anselm; Lohbauer, Ulrich (Journal of Adhesive Dentistry, 2014)
To evaluate the bonding performance of self-adhesive resin cements to zirconia and lithium disilicate in self- and dual-curing modes before and after thermocycling.Rectangular bars (3 mm high, 3 mm wide, 9 mm long) were manufactured from zirconia (Vita In-Ceram YZ for inLab, VITA) and lithium disilicate blocks (IPS e.max Press, Ivoclar Vivadent) (n=240 per material). Zirconia bars were sandblasted (35 ?m Al2O3, 1.5 bar pressure). Lithium disilicate bars were HF etched (20 s, IPS Ceramic Etching Gel, Ivoclar Vivadent) and silanized with ESPE Sil (3M ESPE). Forty bars of zirconia were luted in twos perpendicular to each other as were 40 bars of lithium disilicate using RelyX Unicem Automix 2 (3M ESPE), G-Cem LinkAce (GC Europe) or Maxcem Elite (Kerr) in self- or dual-curing mode. Half of the specimens from each material were submitted to tensile bond strength (TBS) testing after 24-h storage in distilled water at 37°C, and half underwent TBS testing after thermocycling (5000 cycles, 5°C/55°C, 30-s dwell time). Bond strength values for each bonding substrate were analyzed using one-way ANOVA (Student-Newman- Keuls, ?=0.05).On zirconia, dual-curing resulted in significantly (p<0.05) higher tensile bond strengths compared to self-curing, with the exception of RelyX Unicem 2 after thermocycling. Thermocycling significantly (p<0.05) reduced the tensile bond strength of Maxcem Elite to zirconia in both curing modes. The TBS of self-adhesive cements to lithium disilicate showed no significant (p>0.05) difference between the different curing modes and after thermocycling.For most of the investigated self-adhesive cements, bond strengths to zirconia were increased by dual curing; this was not true for lithium disilicate. For luting on zirconia with self-adhesive cements, dual curing is strongly recommended in clinical situations.
EVALuna2:24671

Ultra-high-frequency ultrasound in patients with spinal muscular atrophy: A retrospective feasibility study - Regensburger, Adrian; Wagner, Anna; Hanslik, Gregor; Schuessler, Stephanie C.; Fahlbusch, Fabian; Wölfle, Joachim; Juengert, Joerg; Trollmann, Regina; Knieling, Ferdinand (Muscle & Nerve, 2020)
CRIS-Team WoS Importer:2020-01-17